TRADE OFF RELEVANCE DAN RELIABILITY: ISU IFRS - Hadi Mahmudah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2013)
Financial reports containing qualitative characteristic that are useful for usernya.For a long time believed to bethe existence of trade off between characteristic of qualitative relevance and reliability. Trade off due to the factthat the use of the method of measurement historical cost and fair value. Trade off occur because of the interestsof for the purpose of the preparation of reports on finance. Accountability for the purpose of the measurement ofthe cost of historical still reliable because reflect the truth (objective), on the contrary for the purpose ofinformation in the decision-making process and the value of reasonable more relevant. Trade off betweenrelevant and the reliability of there will always be because there is a difference in the interests of andarrangement of trend setter concerning characteristics qualitative to be undertaken, so the company it is notpossible to showing both of them in coordinated with the same. The existence of trade off between relevant andthe reliability of use on fair value that give preference to relevant and reliability at the expense of resulting infinance reports.